The Convergence of the Formation of Intuitive Knowledge in Mullā Ṣadrā’s Philosophy and Tafsīr al-Ṣāfī & Tafsīr al-Mīzān - Maʿṣūma al-Sādāt Sārī-ʿĀrifī; ʿAlī-Riḍā Kuhansāl (آموزه‌‌های فلسفه اسلامي, 2024)
This research, using a descriptive-analytical approach, explains the factors leading to intuitive certainty (Arabic: یَقینُ الْحُضوری, lit.: certainty by vision) from the perspective of Mullā Ṣadrā’s philosophy and the tafsīrs (Arabic: تَفاسیر, romanized: tafāsīr) al-Ṣāfī (Arabic: الْصَّافِی ) and al-Mīzān (Arabic: اَلْمیزان). The aim of this article is to examine the extent to which Ṣadrā’s philosophy aligns with the interpretations of his commentators in the factors leading to intuitive certainty, and the applicability of this perspective in the exegesis of the Qurʾān. Ultimately, it is revealed that the tafāsīr (plural form of tafsīr, Arabic: تَفْسیر), in analyzing the factors of intuitive certainty, consider three domains: the relationship of intuitive knowledge (Arabic: عِلْمُ الْحُضوری, lit.: knowledge by presence or presential knowledge) with the knower and the known, the knower, and the agent of knowledge (Arabic: اَلْعِلْم, romanized: al-ʿilm). Although they use Ṣadrian principles such as the primacy (principle) of existence (Arabic: أصَالةُ الْوُجُود), gradation (Arabic: تَشْکیک), and substantial motion, this application generally remains at the foundational level. In other words, the tafāsīr content themselves with comprehensive of the relationship of the knower to the known and the moral and behavioral journey of the knower in receiving the investment of intuitive certainty from its origins. They do not address other aspects of the relationship that create certainty in relation to the knower, nor do they delve into the gradation in existence and substantial motion in analyzing (tautologous) the knower, its source, and its relation to the factor of knowledge. Therefore, despite their emphasis on using rational foundations, tafāsīr do not apply these principles in all levels of analyzing intuitive certainty. Thus, the philosophical approach to analyzing intuitive certainty is merely one method among others, without predominance, in these two Mullā Ṣadrā’s commentators’ interpretations.